Large-scale Robotic Fabrication of Polychromatic Relief Glass. (March 2022) - Giesecke, Rena; Dillenburger, Benjamin
This research investigates a new digital fabrication method for large-scale polychromatic glass elements. Glass elements with locally differentiated properties usually require manual labor or are limited to film applications of secondary materials that are incapable of producing material texture and relief in glass. To create mono-material glass elements for buildings with customized color, opacity, and relief present in the same glass element, this research investigates a novel robotic multi-channel printing process for industrial float glass. Mono-material polychromatic glasses do not require any additional material and can be fully recycled. This paper presents a design-to-production workflow for the construction scale within feasible cost. Investigations include kilning and material considerations, multi-channel tool and fabrication setup, tool path generation, process parameter calibration, and large-scale prototyping. The co-occurrence of locally varying opacities, colors, material textures, and relief within one glass element enabled by the presented robotic fabrication method could allow for novel optical and decorative features in facades and windows.